Modeling the impact of nature-based solutions on dry season water availability: exploration of spatio-temporal configurations - Garima Mandavya; Sadie McEvoy; Tolulope Odunola; Umit Taner; Xi Chen; Drew McAvoy; Koen Verbist; Patrick Ray (Journal of Hydrology, 2026)

Towards an improved language for river data analysis: Demonstration for the highly-regulated Ohio River basin - Gaurav Atreya; Todd Steissberg; Drew McAvoy; Xi Chen; Patrick Ray (Environmental Modelling & Software, 2026)

NCBI Orthologs: Public Resource and Scalable Method for Computing High-Precision Orthologs Across Eukaryotic Genomes - Dong-Ha Oh; Alexander Astashyn; Barbara Robbertse; Nuala A. O’leary; W. Ray Anderson; Laurie Breen; Eric Cox; Olga Ermolaeva; Robert Falk; Vichet Hem; J. Bradley Holmes; Patrick Masterson; et al. (Journal of Molecular Evolution, 2025)
Orthologs are fundamental for enabling comparative genomics analyses that further our understanding of eukaryotic biology. The unprecedented increase in the availability of high-quality eukaryotic genomes necessitates scalable and accurate methods for orthology inference. The National Center for Biotechnology Information (NCBI) developed “NCBI Orthologs”, a resource and a computational pipeline designed to meet this challenge within the NCBI RefSeq framework. This system integrates protein similarity, nucleotide alignment, and microsynteny to achieve high-precision ortholog assignments across diverse eukaryotes. The pipeline leverages high-quality RefSeq annotations and processes genomes individually, ensuring scalability. Resulting ortholog data, organized into gene-level anchored sets, enables propagation of functional annotation information and facilitates comparative genomics. Critically, these data are integrated into the NCBI Gene resource, providing users with access from various entry points. The NCBI Datasets resource provides an intuitive interface to explore orthologous relationships on the web and allows bulk data download via the web, command-line tools, and an API. We detail the methodology, including anchor species selection and the decision tree used to arrive at high-confidence one-to-one orthology relationships. NCBI Orthologs is a valuable resource for facilitating functional annotation efforts and enhancing our understanding of eukaryotic gene evolution.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Shifting Patterns in the Weather Regimes That Drive Regional Drought: Demonstration for South Africa - Garima Mandavya; Gaurav Atreya; John Kucharski; Andrew Watson; Nasser Najibi; Koen Verbist; Patrick Ray (International Journal of Climatology, 2025)
Traditional vulnerability assessments of climate change impacts often rely on randomised precipitation scenarios that lack a strong physical science basis. Furthermore, the limitations of General Circulation Models (GCMs) in accurately representing local precipitation fields undermine their utility for projecting future hydroclimatic extremes. To address these gaps in climate risk management, this study explores the role of large‐scale atmospheric circulation patterns, known as weather regimes (WRs), in explaining local and regional precipitation dynamics in South Africa. Utilising a Non‐Homogeneous Hidden Markov Chain approach, we identified six primary WRs for South Africa, each exhibiting distinct seasonal patterns. The results show that winter precipitation near Cape Town is dominated by three WRs linked to higher rainfall, whilst summer precipitation is influenced by two WRs associated with drier conditions. The WR‐precipitation relationship in South Africa appears to be influenced by topographic features (e.g., The Great Escarpment and Cape Fold Mountains) and ocean currents (Agulhas and Benguela), leading to distinct spatial precipitation responses to regional WR configurations. Importantly, significant shifts in seasonal WR frequencies have been observed over the past two decades, particularly a marked change since 2010. Notably, a WR historically associated with rainfall in Cape Town has been replaced by a drier WR, contributing to worsening drought conditions, including the 2015–2017 “Day Zero” drought. During this period, the WR associated with dryness in Cape Town occurred more frequently than the historical average, whilst wetter years before and after the drought were characterised by low‐pressure (low 500 hPa geopotential height anomalies) WRs conducive to precipitation. In contrast, the drought years were dominated by high‐pressure (high 500 hPa geopotential height anomaly) WRs associated with dry conditions. This WR‐precipitation analysis underscores the critical link between atmospheric circulation patterns and regional hydroclimatic extremes. These findings can inform the development of WR‐based rainfall generators, providing valuable tools for vulnerability assessments and climate change adaptation planning.

Impacts of N-(n-Butyl)thiophosphoric triamide (NBPT) on the physicochemical properties of milk protein isolate (MPI) dispersions: A study on micelle integrity - Maria P. Byrne; Patrick J. Forrestal; Tom F. O’ Callaghan; Niharika Rahman; Aishwarya Ray; Martin Danaher; Bernard M. Corrigan; Noel A. McCarthy; Chikere G. Nkwonta; Karl Richards; Farhad Garavand; Enda Cummins; et al. (Food Structure, 2025)

Effects of nitrogen reduction on the agronomic characteristics, quality, and water and fertilizer use efficiency of tomato (lycopersicon esculintum mill.) between drip fertigation and negative-pressure fertigation - Jiajia Wang; Changjun Wang; Huaiyu Long; Ray Bryant; Patrick J. Drohan; Fengchen Qu; Dichuan Liu; Guolong Zhu; Zhuan Wang; Le Wang (Irrigation Science, 2025)

Remote sensing-enabled machine learning for river water quality modeling under multidimensional uncertainty - Saiful Haque Rahat; Todd Steissberg; Won Chang; Xi Chen; Garima Mandavya; Jacob Tracy; Asphota Wasti; Gaurav Atreya; Shah Saki; Md Abul Ehsan Bhuiyan; Patrick Ray (Science of The Total Environment, 2023)

Modelling potential human exposure to the nitrification inhibitor dicyandiamide through the environment-food pathway - Aishwarya Ray; Patrick Forrestal; Chikere Nkwonta; Niharika Rahman; Pilar Byrne; Martin Danaher; Karl Richards; Sean Hogan; Enda Cummins (Environmental Impact Assessment Review, 2023)

Measurement of grass uptake of the urease inhibitor NBPT and of the nitrification inhibitor dicyandiamide co-applied with granular urea - Niharika Rahman; Chikere G Nkwonta; Martin Danaher; Karl G. Richards; Sean A Hogan; Enda Cummins; Macdara O’ Neill; Aishwarya Ray; Maria P. Byrne; Patrick J. Forrestal (Environmental Science and Pollution Research, 2023)

Food security status and breast cancer screening among women in the United States: Evidence from the Health and Retirement Study and Health Care and Nutrition Study - Asos Mahmood; Satish Kedia; Patrick J. Dillon; Hyunmin Kim; Hassan Arshad; Meredith Ray (Cancer Causes & Control, 2023)

Impact of anoxia and oyster mortality on nutrient and microbial planktonic components: A mesocosm study - Julie Le Ray; Béatrice Bec; Annie Fiandrino; Franck Lagarde; Nicolas Cimiterra; Patrick Raimbault; Cécile Roques; Sylvain Rigaud; Julie Régis; Behzad Mostajir; Sébastien Mas; Marion Richard (Aquaculture, 2023)

Rendered materials partly substitute inorganic nitrogen fertilizers and improve nitrogen recovery in maize production system - Bhupinder Singh Jatana; Christopher Ray; Christopher Kitchens; Patrick Gerard; Nishanth Tharayil (Nutrient Cycling in Agroecosystems, 2022)

Correction to: A missense mutation in IFT74, encoding for an essential component for intraflagellar transport of Tubulin, causes asthenozoospermia and male infertility without clinical signs of Bardet–Biedl syndrome - Patrick Lorès; Zine-Eddine Kherraf; Amir Amiri-Yekta; Marjorie Whitfield; Abbas Daneshipour; Laurence Stouvenel; Caroline Cazin; Emma Cavarocchi; Charles Coutton; Marie-Astrid Llabador; Christophe Arnoult; Nicolas Thierry-Mieg; et al. (Human Genetics, 2021)

A missense mutation in IFT74, encoding for an essential component for intraflagellar transport of Tubulin, causes asthenozoospermia and male infertility without clinical signs of Bardet–Biedl syndrome - Patrick Lorès; Zine-Eddine Kherraf; Amir Amiri-Yekta; Marjorie Whitfield; Abbas Daneshipour; Laurence Stouvenel; Caroline Cazin; Emma Cavarocchi; Charles Coutton; Marie-Astrid Llabador; Christophe Arnoult; Nicolas Thierry-Mieg; et al. (Human Genetics, 2021)

Investigating the Mechanical Behavior of Clot Analogues Through Experimental and Computational Analysis - Sarah Johnson; Ray McCarthy; Michael Gilvarry; Peter E. McHugh; J. Patrick McGarry (Annals of Biomedical Engineering, 2021)

Vulnerability and risk: climate change and water supply from California’s Central Valley water system - Patrick Ray; Sungwook Wi; Andrew Schwarz; Matthew Correa; Minxue He; Casey Brown (Climatic Change, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Analysis of genetic diversity of lychee (Litchi chinensis Sonn.) and wild forest relatives in the Sapindaceae from Vietnam using microsatellites - Hoa Tran; Shinya Kanzaki; Ludwig Triest; Inaki Hormaza; Na Jong Kuk; Ray Ming; Jean Bousquet; Damase Khasa; Patrick Van Damme (Genetic Resources and Crop Evolution, 2019)

Consideration of carbon dioxide release during shell production in LCA of bivalves - Nicholas E. Ray; Teri O’Meara; Timothy Wiliamson; Jose-Luis Izursa; Patrick C. Kangas (The International Journal of Life Cycle Assessment, 2018)

The future of nemertean taxonomy (phylum Nemertea) — a proposal - Per Sundberg; Sónia C. S. Andrade; Thomas Bartolomaeus; Patrick Beckers; Jörn von Döhren; Daria Krämer; Ray Gibson; Gonzalo Giribet; Alfonso Herrera‐Bachiller; Juan Junoy; Hiroshi Kajihara; Sebastian Kvist; et al. (Zoologica Scripta, 2016)

Genome-wide association of familial prostate cancer cases identifies evidence for a rare segregating haplotype at 8q24.21 - Craig C. Teerlink; Daniel Leongamornlert; Tokhir Dadaev; Alun Thomas; James Farnham; Robert A. Stephenson; Shaun Riska; Shannon K. McDonnell; Daniel J. Schaid; William J. Catalona; S. Lilly Zheng; Kathleen A. Cooney; et al. (Human Genetics, 2016)

Estimation of flood damage functions for river basin planning: a case study in Bangladesh - Y. C. Ethan Yang; Patrick A. Ray; Casey M. Brown; Abedalrazq F. Khalil; Winston H. Yu (Natural Hazards, 2015)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Impact of acamprosate on behavior and brain-derived neurotrophic factor: an open-label study in youth with fragile X syndrome - Craig A. Erickson; Logan K. Wink; Balmiki Ray; Maureen C. Early; Elizabeth Stiegelmeyer; Lauren Mathieu-Frasier; Vanessa Patrick; Debomoy K. Lahiri; Christopher J. McDougle (Psychopharmacology, 2013)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Sustainable Catchment Managing in a Climate Changing World: New Integrative Modalities for Connecting Policy Makers, Scientists and Other Stakeholders - Ray Ison; Kevin Collins; John Colvin; Janice Jiggins; Pier Paolo Roggero; Giovanna Seddaiu; Patrick Steyaert; Marco Toderi; Chiara Zanolla (Water Resources Management, 2011)

Late Pleistocene to Holocene sedimentation and hydrocarbon seeps on the continental shelf of a steep, tectonically active margin, southern California, USA - Amy E. Draut; Patrick E. Hart; Thomas D. Lorenson; Holly F. Ryan; Florence L. Wong; Ray W. Sliter; James E. Conrad (Marine Geophysical Research, 2009)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Ecological correlates of duckling adoption among white-winged scoters Melanitta fusca: strategy, epiphenomenon, or combination? - Joshua J. Traylor; Ray T. Alisauskas; F. Patrick Kehoe (Behavioral Ecology and Sociobiology, 2008)